1988
DOI: 10.1067/mva.1988.avs0070139
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cigarette smoke, nicotine, and carbon monoxide on the permeability of the arterial wall

Abstract: The association between cigarette smoking and the development of atherosclerosis is well established, but the mechanism that makes cigarettes such a potent "risk factor" is not understood. There is normally a constant insudation of plasma macromolecules into the arterial wall. Fibrinogen and lipids are two of the large molecules involved in atherosclerosis. Therefore we studied the effect of cigarette smoke, nicotine, and carbon monoxide on the permeability of the canine arterial wall to 125I-labeled fibrinoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Similar doses in chronic exposure (> 7 but ≤ 21 days) did not alter extravasation of macromolecules in human pulmonary epithelium (Minty et al . 1984), canine femoral endothelium (Allen et al . 1988), hamster cheek pouch microvessels (Myers et al .…”
Section: Discussionmentioning
confidence: 99%
“…Similar doses in chronic exposure (> 7 but ≤ 21 days) did not alter extravasation of macromolecules in human pulmonary epithelium (Minty et al . 1984), canine femoral endothelium (Allen et al . 1988), hamster cheek pouch microvessels (Myers et al .…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all smokers exhibit raised fibrinogen levels that increase with age [32, 33] and correlations between fibrinogen level and smoking status have previously been described [15, 31, 34, 35]. The plasma fibrinogen level is a significant factor in the genesis of atherosclerotic changes [36–38], and in animal experiments a significant increase in the permeability coefficients, allowing increased permeation of fibrinogen into the vascular endothelium, occurred during administration of tobacco smoke and CO, but not during nicotine infusions [39]. Similarly, one study in humans reported a significant drop in the carboxyhaemoglobin (COHb) level after smoking was discontinued for 3 days (1.70 vs. 5.65%), and the COHb levels did not increase when nicotine was administered via transdermal patches [40].…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco inhalation results in vascular endothelial damage leading to inflammation and increased secretion of cell adhesion molecules with subsequent increased platelet and monocyte adhesion to the vessel wall. The result is to promote atherosclerosis [35–37]. With respect to lipoproteins, smoking disturbs lipoprotein metabolism by increasing insulin resistance and lipid intolerance and is implicated in the production of small‐dense LDL, which is more readily oxidized.…”
Section: Cigarette Smokingmentioning
confidence: 99%